Bullying in the Russian Secondary School: Predictive Analysis of Victimization - Avanesian, Garen; Dikaya, Liudmila; Bermous, Alexander; Kochkin, Sergey; Kirik, Vladimir; Egorova, Valeria; Abkadyrova, Irina (Frontiers in Psychology, 2021)
Background: Bullying has been recognized as an important determinant of personal development in adolescence. Although numerous studies report high prevalence of bullying in Russian schools, limited research was based on the large-scale, nationally representative analysis, which highlights the lack of findings applicable to the national context. Objective: The study aims to address the following research questions: 1) What is the bullying victimization prevalence in Russian secondary schools? 2) What is the socio-demographic profile of the bullying victims? 3) To what extent do learning outcomes in core subject domains predict bullying? 5) How does psychological climate at school affect the occurrence of bullying? 6) Which emotional states do typically the bullying victims display? 7) Which psychosocial traits are the most common for bullying victims? Data and Methods: The study adopts the statistical analysis of the PISA-2018 data in Russia. The final sample consists of 6,249 children aged 15 years old who answered the bullying questions. K-means clustering approach was adopted to identify schoolchildren who should be classified as bullying victims amongst those who has reported bullying. Logistic regression was used to estimate the probability change of bullying under different psychosocial factors and examine effect of bullying on victims' emotional states. Results: The results of the study reveal that 16% of children are victims of bullying in the Russian secondary school. Bullying is strongly associated with learning outcomes in reading, thus outlining that low performers are at risk of severe victimization. Bullying is also contingent on the psychological climate and tends to develop more frequently in a competitive environment. The findings outline that bullying increases negative feelings such as misery, sadness, and life dissatisfaction amongst its victims, making a substantial footprint on their lives. Logically, bullying victims are less likely to feel happy and joyful. Finally, bullying victims tend not to share negative attitudes to the bullying per se, which means that they accept the role of victims and in other context could become perpetrators. Implications: instead of dealing with the consequences of bullying, prevention strategies should aim at facilitating a positive environment at school, thus nipping the problem in a bud.